Religious rhetoric in US right-wing politics - Migliori, Chiara Maddalena (Springer, 2022)
Intro – Preface – Acknowledgments – Praise for Religious Rhetoric in US Right-Wing Politics – Contents – About the Author – 1 The Outsider and the White House – White Conservative Christians, the Religious Right, and Donald Trump: The Creation of a Tale – Scope and Aim – References – 2
Description based on publisher supplied metadata and other sources
Keywords: Electronic books